OPTIMAL REGIMENS OF THE BASAL-BOLUS INSULIN THERAPY IN ADOLESCENTS WITH TYPE 1 DIABETES MELLITUS - G. A. Galkina; A. A. Voropay; M. A. Levkovich; S. V. Vorobiov; M. V. Komkova; N. V. Morozova (Бюллетень сибирской медицины)
This study was aimed to determine peculiarities in regimens of the pump insulin therapy and to reveal the optimal basal-to-bolus insulin ratio that are necessary for achieving optimal glycemic control in adoles-cents with type 1 diabetes mellitus (T1DM).  82 adolescents at the age of 14–18 with T1DM, using continuous subcutaneous insulin infusion (CSII) from 5 months to 7.5 years were monitored with continuous glucose monitoring (CGM) system «Guar-dian Real Time» or CGM system, built in MiniMed Paradigm Revel System 722 (Medtronic Minimed, USA). Assessing the quality of glycaemic control was based on the level of glycated haemoglobin (HbA1c). The results of CGM were reviewed and average for 3 days performances: total daily dose of insulin, dose of basal and bolus insulin, basal-to-bolus insulin ratio, carbohydrate content of the meal, expressed in BE, carbohydrate ratio, insulin sensitivity factor were determined. The patients were subdivided into 2 groups: group 1 – adolescents with the optimal/suboptimal glycemic control (n = 55), 2 – adolescents with long-standing poorly controlled T1DM (n = 27). Average total daily dose of basal insulin (U in a day, U per kg in a day) in adolescents group 1 was significantly higher, com-pared with patients in group 2 (р = 0.043; р = 0.038 respectively). Patients in group 2 received more car-bohydrates with a meal intake and had higher doses of average total daily bolus insulin. The average ba-sal-to-bolus ratio from group 1 patients was 51/49%, compared with group 2 patients – 45/55% (р = 0.026).  An important condition for achieving optimal glycemic control is a high level of compliance and skills of adolescents. Optimal well-balanced basal-to-bolus insulin ratio in adolescents with T1DM on CSII, which can provide improvements in blood glucose management and reducing the risk of complications of the disease, is 51/49%.